(untitled) (Research, Society and Development, 2021)
The purpose of this protocol is to ensure the transparency of the scoping review process, pre-defining the objectives, methods, eligibility criteria and relevant data related to adverse reactions on the oral mucosa and face caused by natural products. It was registered in the Open Science Framework and developed in accordance to the methodological recommendations of the Joanna Briggs Institute Manual. The search strategy will be structured for the PubMed and later adapted to other databases, such as Scopus, Web of Science, Embase, LILACS and LIVIVO, in addition to gray literature (Google Scholar and OpenGrey), using the following terms and their related words: “Biological Products”, “Natural Products”, “Phytotherapy”, “Chemical Burn”, “Adverse Effect”, “Oral mucosa” and “Face”. Additionally, the reference lists of the included articles will be searched. Case reports that present adverse reactions to the oral mucosa and the face, with no gender, age or ethnicity distinction will be included in this review. Clinical, in vitro, and animal models studies, literature reviews and opinion articles will be excluded. The selection will be conducted in two phases by two independent examiners and a third reviewer will resolve disagreements. Data will also be extracted independently, using a form developed by the authors, and presented as tables and/or figures and as a narrative form. This protocol will assist in the development of the scoping review, for mapping and summarizing the evidence.